Prediction of the overall mechanical response of gradient nano-grained materials based on grain size distribution profile. (1st July 2022) - Yu, Li
Highlights: Analytical relation between strain gradient and grain size gradient were studied. The accumulated strain gradient can influence the increment of strain gradient. The overall mechanical response can be predicted based on the grain size distribution profile. This model can be utilized to optimize the GNG materials design. Abstract: Inspired by the gradient structure of biological materials, various gradient nano-grained (GNG) materials, inside which grain size spans several orders of magnitude, have been manufactured in recent years. This kind of material often exhibits extra hardening ability and ultimately achieves synergetic strength and ductility. The extra hardening of GNG materials is closely related to the strain gradient formed during deformation. However, the analytical relation between the structural gradient, strain gradient is still unexplored. Besides, the previous works focused on only one type of GNG material, and the understanding of the effect of different kinds of microstructures is limited. This paper explores the analytical relations between the strain gradient and the average grain size, as well as the grain size gradient in GNG materials. The overall mechanical responses of GNG interstitial-free (IF) steel and GNG Ni are well predicted. The results verify that the extra hardening of GNG materials is dependent on their unique microstructures. The strength and ductility of GNG materials can be improved by adjusting the composition and distribution of coarse grains and nano-grains.